Perlaksanaan Model Kurikulum Turath di Maahad Tahfiz Integrasi Negeri Selangor - Zetty Nurzuliana Rashed; Mardhiah Yahaya; Norfariza Mohd Radzi; Mohd Faeez Ilias; Mohd Fakhri Sungit; Ainul Hayat Abdul Rahman (USIM Press, 2024)
Vol. 5 No. 1 (2021)